Monitoring construction quality management systems: quality cost-benefit analysis - Vitor Abrantes Almeida (2004)
In a global market characterized by competitive and higher demands, the construction companies' life depends on the simultaneous satisfaction of shareholders, clients and employees. According to these strategic objectives, each organization must implement an operational quality management system that identifies, describes and regulates all key processes present. If the quality management system is well structured and conveniently adapted to the reality of the construction sector, it looks like an integrated planning tool. In this case, the quality management system leads the construction company to be more efficient and to create the necessary conditions for a supported continuity. The blueprints are decisive to the building's final quality as well as the execution plan of the financial and logistical perspectives. Processes monitoring allows the measurement of the management system effectiveness and makes it possible to identify specific actions aiming to increase the continuous improvement of the organization. To actualize this proposal, construction companies must conceive and use management indicators. Using specific indicators based on eventual construction defects, delays, increased costs, accidents and deficient relationships between different people involved, it is possible to determine the construction's quality level. Otherwise, using a global indicator it is possible to determine the enterprise's quality level and make it possible to calculate the benefits resulting from the implementation of its quality management system. In this paper we will describe a method for the quality management system monitoring and it is shown its importance for measuring the benefits of the quality management in construction companies